An open-label study of the tolerability and potential efficacy of memantine for treating refractory chronic cough. Issue 3 (20th September 2021) - Abdulqawi, Rayid; Satia, Imran; Holt, Kimberley J.; Dockry, Rachel; Sen, Shilpi; Smith, Jaclyn A.
Refractory chronic cough (RCC) is defined as cough lasting longer than 8 weeks either in the absence of an identifiable underlying cause or that remains resistant to treating any potential underlying causes [1]. Affected patients have a poor quality of life and suffer from fatigue, disturbed sleep, incontinence, frustration, anxiety, and depression [2]. Despite being a debilitating condition, no licensed treatment is available. Blocking NMDA receptors with memantine in refractory chronic cough patients is poorly tolerated and demonstrates no improvement in cough https://bit.ly/3kgx2g1